Effectiveness and cost-effectiveness of incentives as a tool for prevention of non-communicable diseases: A systematic review. (July 2019) - Finkelstein, Eric A.; Bilger, Marcel; Baid, Drishti
Abstract: The rising epidemic of non-communicable diseases (NCDs) poses substantial health and economic challenges to both individuals and society. Application of incentive-based strategies based on traditional and behavioural economic theory has emerged as a potential strategy to address rising rates of NCDs. Yet, whether or not incentives truly represent a promising strategy for addressing NCDs has not been systematically addressed nor is it clear whether certain behavioural economic strategies outperform others or simply offering a cash-based incentive for meeting a goal. In this systematic review we aim to determine whether there is an evidence base for any of these strategies. Forty-eight published randomized controlled trials (70 contrasts) evaluating the effectiveness of incentive-based strategies for improvements in NCD risk-factors were reviewed. Our primary conclusion is that there is a lack of compelling evidence that incentives of any form represent a compelling NCD reduction strategy. More evidence for long-term effectiveness and cost-effectiveness is needed to justify third party funding of any incentive based strategy. Highlights: Preventing non-communicable diseases is a major public health challenge. Incentives based on behavioural economic theory have been proposed as one solution. Results reveal that evidence to support this claim is both limited and mixed. There is a lack of evidence that incentives of any form are cost-effective.